Preoperative oral probiotics relieve insulin resistance and gut dysbacteriosis in patients with gastric cancer after gastrectomy - Weidong Liu; Cihua Zheng; Qiang Li; Tian Xu; Wenjie Cao; Meng Shi; Feng Huang; Lulin Liu; Yufeng Luo; Wenming Zhang; Qun Xiao; Zhaoxia Liu; et al. (Journal of Functional Foods, 2023)
Gastrectomy can improve the clinical survival rate of gastric cancer patients, while the metabolic disorders caused by gastrectomy, seriously affect the postoperative recovery. In this study, probiotics (including Bifidobacterium infantis, Lactobacillus acidophilus, Enterococcus faecalis and Bacillus cereus) were used before gastrectomy to explore the effect of probiotics on gastrectomy patients. Our outcomes revealed probiotics could alleviate postoperative inflammation (Leukocyte; P < 0.05), improve the metabolic disorder (fasting glucose; fasting insulin; HOMA-IR; P < 0.05), reduce the incidence of postoperative insulin resistance (IR; P < 0.001) and infectious complications (P < 0.05). Besides, the probiotics greatly enriched the relative abundance of bacteria Faecalibacterium prausnitzii and Gemmiger formicilis, while decreased the pathogenic Bacteroides fragilis, Prevotella copri and Clostridium difficile at the species levels. Therefore, we believe that preventive use of probiotics can reduce postoperative inflammation, alleviate metabolic disorder, reduce insulin resistance, restore intestinal microecological balance, and finally promote early recovery of patients.